The role of cancer information seeking behavior in developing and disseminating effective smoking cessation strategies: A comparison of current smokers, former smokers, and never smokers. (1st March 2013) - Mathur, Sunil; Levy, Marian; Royne, Marla B
<x xml:space="preserve">Abstract</x> Consumers seeking information about their health may use various resources available and may process information differently. Although behavioral and pharmacological methods are effective in reducing smoking behavior, it is unclear how individual characteristics related to cancer seeking information behavior would be useful in developing and disseminating effective smoking cessation programs. The study used the Health Information National Trends Survey (HINTS) 2007 survey in which data were collected from 7674 respondents. We used separate multinomial regressions to assess differences in trust of doctors and family/friends across smoking status, race/ethnicity, age, and education. Current smokers will likely be the most skeptical about the information presented to them; however, they trust doctors the most, followed by family/friends. Non-Hispanic Blacks have higher proportions of current smokers and lack of trust in information sources. Age and education were significant predictors overall for the model. Current smokers engage in the lowest levels of cancer information search and possess the lowest levels of trust and present challenges in reaching them with important health information. Public health officials should look at community programs that engage medical professionals and encourage individuals to participate in such programs with their friends. Non-Hispanic Blacks present the greatest priority for developing salient strategies and messages for cessation. Communication interventions should focus on the prevention of diseases, and protection and maintenance of public health in the smoking status context, and designed to help smokers quit.